PENGARUH PERBEDAAN LAMA WAKTU PENYIMPANAN PAKAN BERPROBIOTIK TERHADAP KUALITAS PAKAN - Diko Khairil Harianto; ade dwi sasanti; mirna fitrani (Jurnal Akuakultur Rawa Indonesia, 2016)
ABSTRACT Feed had been given probiotics expected can be stored in long periods of time, so that at the time of granting feed time and energy used more efficiency The addition of probiotics on feed with the process of a long storage can improve the quality of fish feed through the solution of ingredients that could not be digested by the body of fish like cellulose, hemiselulosa into simpler sugars that easily digestible with the help of microorganisms. The purpose of this research to know the difference a long time storage of the feed probiotic on the quality of feed. The research had been conducted in Laboratorium Dasar Perikanan, Departement of Aquaculture, Agriculture Faculty, Sriwijaya University on January until March 2016. The research method used a Completely Randomized Design with four treatments and three replications (P1 : pellets probiotics with incubation time 24 hours, P2 : pellets probiotics with incubation time 7 days, P3 : pellets probiotics with incubation time 14 days, P4 : pellets probiotics with incubation time 21 days). Parameters that had been observed were physical pellets condition, nutrition pellets composition, lactat acid bacteria of population, buoyancy feed and destructive power feed. The result showed that physical feed where the treatment P2 covering texture, color and smell feed still in good condition. In the nutrition feed the treatment P4 increases nutrition feed of protein 18,14 %, fats 7,55 % and dust 12,04 %. The population of lactat acid bacteria similar detected between treatment but the population highest in P4 treatment 161,78. In buoyancy and the destructive power the highest was in treatment P1 which was during 428.18 minutes and 318.12 minutes. Â  Key words : Probiotic, Feed , Lactat Acid Bacteri